Sedimentation rates in Atibaia River basin, São Paulo State, Brazil, using Pb-210 as geochronometer - Sabaris, T. P. P. [UNESP]; Bonotto, Daniel Marcos [UNESP] (Pergamon-Elsevier B.V. Ltd, 2011)
The constant initial concentration (CIC) of unsupported/excess Pb-210 model was successfully used to assess Pb-210 data of nine sediment cores from Atibaia River basin São Paulo State Brazil The Pb-210-based apparent sediment mass accumulation rates ranged from 47 7 to 782 4 mg/cm(2) yr whereas the average linear sedimentation rates between 0 16 and 1 32 cm/yr which are compatible with the calculated sediment mass fluxes i e a higher sediment mass accumulation rate yielded a higher linear sedimentation rate The higher long-term based accumulation rate tended to be found in topographically softer regions This occurs because the sediments are preferentially transported in topographically steeper regions instead of being deposited Anthropic activities like deforestation possibly interfered with the natural/normal sedimentation processes which increased in accordance with modifications on the channel drainage The radionuclide geochronology as described in this paper allows determination of sedimentation rates that are compatible with values estimated elsewhere The adoption of an appropriate factor generated from previous laboratory experiments resulted in a successful correction for the Rn-222-loss from the sediments bringing the estimate of the parent-supported (in-situ produced) Pb-210 to reliable values required by the CIC model (C) 2010 Elsevier Ltd All rights reserved
Keywords: Pb-210 geochronology; Sedimentation rate; Alpha spectrometry; Atibaia River basin